The Effect of Liquidity, Profitability, Company Size, Leverage and Age of Company Listings on the Completeness of Internet Financial Reporting Information - Adinata Tenardi, Yoel (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Company as an entity has an obligation to conduct financial reporting, along with the rapid growth of information technology in recent years, manual financial reporting is no longer adequate. Companies that have been listed on the Indonesia Stock Exchange (IDX) are required to conduct financial reporting either manually (hardcopy) or electronically (softcopy) through the company's official website. Financial reporting through the company's website is also known as Internet Financial Reporting (IFR). Therefore, this study aims to test and analyze the factors that affect the completeness of the company's IFR information. This research was conducted quantitatively using independent variables namely liquidity, profitability, company size, leverage and company listing age, while the dependent variable of this research is Internet Financial Reporting. The type of data used is quantitative data in the form of financial statements on the IDX website and the website of each company. The method of data collection is documentation. The research object is a service sector company registered in the IDX in 2017-2019. Data analysis is performed with multiple linear regression analysis. The results showed that the size of the company has a positive effect on the completeness of IFR information. This means that the larger the size of the company, the company will present IFR with more adequate information on the company's website. The test results also proved that leverage negatively affects the completeness of IFR information. This indicates that the greater the leverage of the company, the company will present IFR with lower completeness of information on the company's website. The test results also showed that liquidity, profitability and listing life had no effect on the completeness of IFR information.